Pencapaian Diferensiasi Produk Melalui Strategi Inovasi dan Kreativitas Usaha Mikro Kecil dan Menengah - Fajri, Annisa; Suharti; Purwanto, Dedik (UNIB Press, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, but often face challenges such as limited access to technology, quality of human resources, and marketing. This community service activity aims to help MSMEs achieve product differentiation through innovation and creativity strategies. The methods used include theoretical training and practical workshops. The results of the activity showed an increase in participants' knowledge and skills in developing innovative products and creative marketing strategies. Evaluation through questionnaires and interviews showed participant satisfaction and increased sales after implementing new strategies. Challenges faced included limited resources and time, which were overcome through collaboration with related institutions and follow-up programs. Thus, this activity succeeded in increasing the competitiveness of MSMEs in local and international markets, as well as contributing to the national economy. The sustainability of the program is pursued through ongoing mentoring programs and the formation of MSME innovation communities. These results show that innovation and creativity strategies can be an effective solution to overcome the challenges faced by MSMEs and improve community welfare.